PEMANFAATAN SIMULATOR TINA-TI UNTUK ANALISIS RANGKAIAN MESH DAN PERBANDINGANNYA DENGAN EKSPERIMEN AKTUAL - Jannah, Nusaibah Fathul; Fuada, Syifaul; Hasugian, Leonardi Paris; Heong, Yee Mei (Jurnal Kajian Teknik Elektro, 2024)
A simulator is a tool designed to replicate the operations of real-world equipment to aid users in understanding and utilizing them. However, the results of simulator computation often differ slightly from those generated by theoretical calculations. To tackle this issue, various techniques, including theoretical calculations, circuit simulation, and experimentation, are utilized to identify and analyze discrepancies in calculation results between simulators and real-world experiments. This study focuses on TINA-TI, a widely used software for simulating electrical circuits. Specifically, the research examines the analysis of a 3-loop mesh circuit comprising resistors and voltage sources. Four distinct 3-loop mesh circuits are investigated using a multi-step research methodology involving theoretical circuit analysis, simulation on TINA-TI, and practical experiments on a project board. The findings indicate that TINA-TI can accurately simulate straightforward, branched electrical circuits like mesh circuits. However, inconsistencies exist between theoretical forecasts and experimental observations, such as variations in polarity and numerical discrepancies, with certain measurements displaying significant deviations. The aim of this research is to provide insights into the assessment of simulators for simulating basic electrical circuits and to encourage further exploration of the TINA-TI simulator.